The Influence of Leadership, Supervision and Work Motivation on Employee Work Effectiveness with Work Discipline as Intervening Variable: Pengaruh Kepemimpinan, Pegawasan dan Motivasi Kerja Terhadap Efektivitas Kerja Karyawan dengan Disiplin Kerja sebagai Variabel Intervening - Fawaid, Muhammad; Ubaidillah, Hasan (Universitas Muhammadiyah Sidoarjo, 2023)
The purpose of this study was to determine and analyze the influence of leadership, supervision and work motivation on work effectiveness with work discipline as an intervening variable at UD. Ridzil Jaya Utama. The research uses a quantitative approach. The sample in this study were all UD employees. Ridzil Jaya Utama with a total of 60 people. Collecting data in this study in the form of a questionnaire. The data analysis technique was carried out using path analysis using partial hypothesis testing, simultaneous testing, multiple correlation coefficient tests and multiple determination coefficients. The results showed that: 1) Leadership had an effect on work effectiveness, 2) Leadership had an effect on work effectiveness with work discipline as an intervening variable, 3) Supervision had an effect on work effectiveness with work discipline as an intervening variable, 4) Supervision had an effect on work effectiveness with discipline. work as an intervening variable, 5) work motivation affects work effectiveness, 6) motivation affects work effectiveness with work discipline as an intervening variable, and 7) work discipline affects work effectiveness.